A natural history of human emotions - Walton, Stuart (New York : Grove Press, 2004)
Explores the ten basic human emotions that shape personality and identity, blending insights from philosophy, science, history, and popular culture.
Originally published: London : Atlantic Books, 2004.
Includes bibliographical references and index.
Keywords: Emotions